A case study of solid waste management in Malaysia: Issues, challenges and its business management practices - Mat Zin, Rosliza; Othman, Siti Norezam; Abdullah, Zarifah (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2016)
The paper aims to explore the business management practices and the implications for its use in tackling the issues and challenges faced by a solid waste management company in Malaysia, FreshAir. Experiencing rapid industrialization, with warm climate and high humidity, Malaysia is exposed to serious environmental and health related hazards. The case study research used semi-structured interviews conducted with the key participants of FreshAir in order to understand the use of business management techniques in tackling the issues and challenges faced by the solid waste company. Waste implies unwanted resources, which clearly create additional environmental costs and health related issues if they are not well managed. The study proposed that to sustain and remain competitive, organizations must ensure that the issues and challenges they face are managed effectively, which can be achieved by adopting relevant business and management accounting techniques. The findings suggest that the primary purpose of having business management and accounting information is to help FreshAir to make appropriate decisions to tackle the issues and challenges in solid waste management. The business management practices of FreshAir serve as an integral part of strategic, operations management and quality management, which lead to its sustainability. The study is of benefit to academics and managers by implying that the management functions of planning, organizing, directing and controlling should be in place to support sustainable waste management solutions.